2019
DOI: 10.1080/01416200.2019.1635434
|View full text |Cite
|
Sign up to set email alerts
|

‘Science is purely about the truth so I don’t think you could compare it to non-truth versus the truth.’ Students’ perceptions of religion and science, and the relationship(s) between them: religious education and the need for epistemic literacy.

Abstract: There already exists a large knowledge base about teaching and learning related to the origins, diversity and history of life on Earth. We know less about teaching and learning related to wider issues pertinent to both religion and science. In our research with 40 students in six secondary schools in England, we looked at wider issues of student perceptions of religion and science. Our study involved an intervention of six lessons in Science and six in Religious Education (RE). Issues of philosophy, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…In the present study, we observed that concepts such as 'worldview' were foreign to most students. We consider that Religious Education needs to pay attention to epistemic literacy if we aim to avoid epistemological misconceptions and enable students to develop their knowledge about the specific forms of knowledge manifested in religions (Pearce et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observed that concepts such as 'worldview' were foreign to most students. We consider that Religious Education needs to pay attention to epistemic literacy if we aim to avoid epistemological misconceptions and enable students to develop their knowledge about the specific forms of knowledge manifested in religions (Pearce et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The closest example is Duveen and Solomon's (2007) account of role-playing a fictional blasphemy trial for Darwin, though this focused on historical empathy. However, there has long been research interest in argumentation more generally across science and religious education, especially around etiological and ethical issues (Fuchs, 2009;Basel et al, 2014;Weiß, 2016), around the broader epistemic differences (e.g., Billingsley et al, 2012;Pearce et al, 2019), or the challenges facing religious students or teachers (e.g., Dodick et al, 2010).…”
Section: Argumentation and Perspective-taking: Research In Religious Education And Sciencementioning
confidence: 99%
“…Science and religion can be seen as antithetical (e.g., Dawkins, 2006), and some argue that this also applies educationally (Mahner & Bunge, 1996). Indeed, students do not come unknowingly to lessons that tackle this relationship, often having pre-existing opinions (Taber et al, 2011;Hoven, 2015;Pearce et al, 2019), so this interdisciplinary arena offers rich potential for exploring the interaction between argumentation and perspective-taking. However, this project is based in England, where an impartial study of different religions and worldviews prevails in religious education, thus avoiding some of the conventional science and religion debates (see Hanley et al, 2014), but also raising new questions about argumentation and perspective-taking.…”
Section: Introductionmentioning
confidence: 99%
“…Weiss's (2016) use of Keinpointner (1983). One difference between English and German-language research is that RE in German-speaking countries is largely confessional, and therefore rooted in a theological tradition, and these studies lie within a broader field of research on students' and teachers' attitudes to religion and science, which implicitly invokes argumentation, including studies of 'epistemic literacy' (Pearce, Stones, Reiss, and Mujtaba 2019), and 'epistemic insight' (e.g. Billingsley et al 2013;Billingsley, Riga, Taber, and Newdick 2014;Hanley, Bennett, and Ratcliffe 2014; see also Astley and Francis 2010).…”
Section: Argumentation In Religious Educationmentioning
confidence: 99%